Safety assessment of mixtures of 1,9‐nonanediamine (NMDA) and 2‐methyl‐1,8‐octanediamine (MODA), for use in food contact materials - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Andrew Chesson; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; et al. (EFSA Journal, 2024)
Abstract The EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP) assessed the safety of mixtures of 1,9‐nonanediamine (NMDA) and 2‐methyl‐1,8‐octanediamine (MODA) when used to produce polyamide food contact materials for contact with all food types for long‐term storage at room temperature and below, including heating up to 121°C for up to 2 h. The polyamide material is also intended to be used for repeated use up to 121°C with short contact (up to 30 min). The polymer typically contains ■■■■■ of a low molecular weight fraction (LMWF, < 1000 Da). The specific migration was measured with polyamide samples in a set of migration tests with 3% acetic acid and 10% ethanol. NMDA and MODA were not detected at ■■■■■, respectively. The specific migration of the LMWF consisting of NMDA/MODA‐related species was up to ■■■■■. The overall migration in olive oil was below the detection limit (3 mg/dm2). The most abundant migrating LMWF oligomers were identified. Toxicological studies were performed with NMDA, MODA and with polyamide formulations enriched in the LMWF. The results of genotoxicity assays did not raise a concern. From a repeated‐dose oral 90‐day toxicity study in rats, the Panel identified a no observed adverse effect level (NOAEL) of 1000 mg/kg body weight per day for the migrating LMWF. The CEP Panel concluded that NMDA/MODA mixtures do not raise a safety concern for the consumer when used as comonomer with terephthalic acid to manufacture polyamide articles intended for contact with all food types, except for infant formula and human milk, if the migration of NMDA and MODA does not exceed 0.05 mg/kg food (as a sum of the two substances) and if the migration of the LMWF consisting of NMDA/MODA‐related species does not exceed 5 mg/kg food.